2023
DOI: 10.2147/cia.s386563
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Demographic Characteristics of Centenarians versus Other Age Groups Over 75 Years with Hip Fractures

Abstract: Objective The primary objective was to describe the clinical characteristics, management, and outcomes of centenarians with fragility hip fracture and compare them to other age groups. The secondary objective was to determine the variables associated with length of stay, in-hospital mortality and 30-day mortality. Materials and Methods This is a secondary analysis of the Spanish National Hip Fracture Registry. We included patients ≥75 years admitted for fragility hip fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…Advancing age leads to several clinical and epidemiological differences between young and elderly patients. Even among the elderly, age groups should be considered in the patient’s clinical management, since studies have shown differences in clinical profile and outcomes when comparing different age groups among patients aged 60 or older 9 , 10 , 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Advancing age leads to several clinical and epidemiological differences between young and elderly patients. Even among the elderly, age groups should be considered in the patient’s clinical management, since studies have shown differences in clinical profile and outcomes when comparing different age groups among patients aged 60 or older 9 , 10 , 11 .…”
Section: Discussionmentioning
confidence: 99%